Quantitative flow ratio virtual stenting and post stenting correlations to post stenting fractional flow reserve measurements from the DOCTORS (Does Optical Coherence Tomography Optimize Results of Stenting) study population. Issue 6 (25th November 2019) - Rubimbura, Vladimir; Guillon, Benoit; Fournier, Stéphane; Amabile, Nicolas; Chi Pan, Chan; Combaret, Nicolas; Eeckhout, Eric; Kibler, Marion; Silvain, Johanne; Wijns, William; Schiele, Francois; Muller, Olivier; et al.
Abstract: Objective: We sought to evaluate the correlations of pre‐PCI QFR analysis with virtual PCI called residual QFR and post‐PCI QFR compared to post‐PCI FFR. Background: Quantitative flow ratio (QFR) is a computation of fractional flow reserve (FFR) based on angiography without use of a pressure wire. The ability to evaluate post‐PCI FFR using pre‐PCI QFR analysis with a virtual PCI and the correlation between post‐PCI QFR compared to post‐PCI FFR remains unknown. Methods: From the DOCTORS (Does Optical Coherence Tomography Optimize Results of Stenting) study population, we blindly analyzed residual QFR and post‐PCI QFR from angiographies and compared them to post‐PCI FFR. Results: Ninety‐three post‐PCI QFR measurements and 84 pre‐PCI residual QFR measurements were compared to post‐PCI FFR measurements. No significant difference were observed between mean post‐PCI FFR value (0.92 ± 0.05) compared to mean residual (0.93 ± 0.05) QFR and between mean post‐PCI FFR value compared to mean post‐PCI QFR values were (0.93 ± 0.05) ( p  > .05 for both). The correlation coefficient of residual QFR with post‐PCI FFR was 0.68 (95% CI: 0.53–0.78) and the correlation coefficient of post‐PCI‐QFR with post‐PCI FFR was 0.79 (95% CI: 0.70–0.86). Conclusions: Residual QFR corresponding to pre‐PCI QFR analysis with virtual PCI, and post‐PCI QFR analysis, correlated well with post‐PCI FFR. Further studies are needed to prospectively validate a QFR‐guided PCI strategy.